Determination of Design Criteria for Composite Drive Shaft in Automobiles - Altin, Beytullah; Altinbay Bekem, Aylin; Unal, Ahmet (GAZI UNIV, 2024)
Thanks to their superior properties such as light weight, higher strength and stiffness, corrosion resistance, the use of plastic matrix composites become attractive in many applications. The weight reduction in the automotive sector is one of these applications. By use of plastic matrix composites, weight and CO2 emission reduction in automobiles could be achieved easily. In this study, carbon fiber and epoxy matrix were processed via filament winding method to produce composite drive shaft. Prior to production, finite element modeling were performed to determine the safest design parameters. Various winding angles were analyzed under torsional loading and number of layer was determined according to the failure index and strength ratio criteria. As a result of the numerical analysis, it was seen that the design with the minimum cost in terms of strength was the 10-layer model with a winding angle of +/-45 degrees. To validate the design, the composite shaft was produced with the determined configurations and tested. The fiber volume fraction and the void content of the produced composite were found as similar to 46% was similar to 0.28%, respectively. No plastic deformation was observed in the torsion test. In the flattening and drift-expansion tests, plastic deformation occurred at 39 kN and 106.5 kN, respectively. Compared with a steel shaft, the obtained composite shaft has an 80% reduction in weight, and this could lead to a 1% fuel saving in passenger vehicles.
Keywords: Composite drive shaft; CO2 emission; filament winding; weight reduction; MANUFACTURE; EMISSIONS; STRENGTH; BEHAVIOR; Engineering